RANCANG BANGUN APLIKASI KAMUS TEGAL – INDONESIA BERBASIS ANDROID (Information Technology and Telematics, 2015)
Abstract Tegal Java language is one of the Javanese language dialects spoken in Tegal and surrounding areas. Including local Tegal, Central Java near the western border. Location of existing Tegal northern coast of Java, also in the border area of Central Java and West Java, makes existing Tegal dialect different from other regions. Currently there are still many people who do not know about Tegal language vocabulary. Due to the lack of a dictionary in the form of a practical application are used. Therefore made Tegal Indonesian Dictionary app is based on Android. The method used to create or develop new software is the prototype model (Pressman.1992). This method is a method in which the results of the analysis of the development of a system partially implemented directly into a model without having to wait the entire system is complete in the analysis. The results of this study are Tegal Indonesian Dictionary application based on android that can be used to quickly search vocabulary and practical. Keywords : Dictionary , Tegal language, Indonesia language , Android.